Dynamic response evaluation of the Shanghai Tower in along- and across-wind directions during super typhoon Lekima. (15th April 2023) - Xie, Bo; Luo, Xiaoqun; Zhang, Qilin; Ding, Jiemin
Abstract: The dynamic responses of the Shanghai Tower (ST) under Typhoon Lekima in 2019 were evaluated in the along- and across-wind directions based on SHM data. Compared to most similar studies that focus on two main axes of the buildings, this study focused on such dynamic responses in the along- and across-wind directions; these processes were also widely discussed regarding wind tunnel tests. The results of dynamic responses in wind directions were compared to those in the main axes of buildings. The vibration amplitudes in the along- and across-wind directions were closer than those in the two main axes. The relationship between acceleration amplitudes and reduced wind speeds showed a significant effect of the vortex shedding. Additionally, time-varying frequency spectra were used to discuss the modal contribution of the vibration signal. The fundamental frequencies and damping ratios were identified using the SSI method, and correlation analyses were carried out. The relationship between the identified damping ratios and the reduced wind speeds exhibits different aerodynamic effects in the along- and across-wind directions. Comparison of the data showed that dynamic response evaluation in the along- and across-wind directions was more suitable to analyze the wind-resistant performances of super high-rise buildings. All results can aid in understanding the characteristics of these interactions as well as perfect the wind-resistant design of super high-rise buildings. Highlights: Vibration strength in along-wind and across-wind directions are close under strong winds. The structural stiffness in the across-wind direction is more sensitive to the variation of wind-induced vibrations. Strong correlations are existed between dynamic parameter indices and vibration amplitudes in the across-wind direction. More specific phenomenon could be investigated along wind directions compared to those in main axes of buildings.